Negative electrode active material for secondary battery, and secondary battery

By introducing phosphorus elements into the silicate composite particles used for the negative electrode in the secondary battery, the electron conductivity of the silicon phase is improved, and the problem of low charge and discharge efficiency in the early stage is solved, and efficient battery performance is achieved.

CN119790510APending Publication Date: 2025-04-08PANASONIC INTELLECTUAL PROPERTY MANAGEMENT CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202380062564.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-08-29
Filing Date
2023-07-18
Publication Date
2025-04-08

AI Technical Summary

Technical Problem

In the existing secondary batteries, the negative electrode active substance containing silicon has the problem of low initial charge and discharge efficiency, especially the large irreversible capacity, which leads to a low ratio of the primary discharge capacity to the primary charge capacity.

Method used

By introducing phosphorus elements into the silicon phase, the electron conductivity of the silicon phase is improved, thereby improving the powder resistivity of silicate composite particles and enhancing the initial charge and discharge efficiency.

Benefits of technology

By making the silicon phase contain phosphorus elements, the electron conductivity of the silicate composite particles improves, and the initial charge and discharge efficiency is improved, while reducing cracking and rupture of the silicate composite particles.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119790510A_ABST
    Figure CN119790510A_ABST
Patent Text Reader

Abstract

This negative electrode active material for a secondary battery is provided with silicate composite particles containing a silicate phase and a silicon phase, the silicon phase being dispersed in the silicate phase, and the silicon phase containing elemental phosphorus in addition to silicon.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention mainly relates to the improvement of negative electrode active materials for secondary batteries. Background Art

[0002] In recent years, secondary batteries such as non-aqueous electrolyte secondary batteries are expected to be used as power sources for small civilian applications, power storage devices, and electric vehicles due to their high voltage and high energy density. In the process of requiring high energy density of batteries, materials containing silicon (Si) alloyed with lithium are expected to be used as negative electrode active materials with high theoretical capacity density.

[0003] However, since the irreversible capacity of the silicon-containing material is large, there is a problem of low initial charge and discharge efficiency (especially the ratio of the initial discharge capacity to the initial charge capacity). Therefore, various technologies have been proposed to pre-introduce lithium equivalent to the irreversible capacity into the silicon-containing material. Specifically, it is proposed to use composite particles containing a lithium silicate phase and silicon particles dispersed in the lithium silicate phase. Silicon particles contribute to the charge and discharge reaction (reversible absorption and release of lithium). The composite particles are manufactured, for example, by sintering a mixture of glassy lithium silicate powder and silicon particles in a high temperature and high pressure atmosphere.

[0004] Patent document 1 proposes "a negative electrode active material for a non-aqueous electrolyte secondary battery, which comprises a mother particle having a silicate phase and silicon particles dispersed in the silicate phase, wherein the silicate phase contains Li, Si and Mx (Mx: an alkali metal, an alkaline earth metal, an element other than Si), and the content of each element relative to the total of the elements other than oxygen in the silicate phase is Li: 3-45 mol%, Si: 40-78 mol%, Mx: 1-40 mol%. " The Mx contains at least one of Al, B, Bi, Sb, Ge, Zr, Ti, P, V, W and La. Patent document 2 proposes "a negative electrode active material for a secondary battery, which comprises a silicate composite particle containing silicon particles and a silicate phase, wherein the silicon particles are dispersed in the silicate phase, and the silicon particles contain at least one first element selected from germanium and aluminum."

[0005] Prior Art Literature

[0006] Patent Document 1: International Publication No. 2019 / 065766

[0007] Patent Document 2: International Publication No. 2021 / 153078 Summary of the invention

[0008] Problems to be solved by the invention

[0009] One of the objectives of the present disclosure is to improve the initial charge and discharge efficiency by increasing the electronic conductivity of the silicon phase.

[0010] Means for solving problems

[0011] One aspect of the present disclosure relates to a negative electrode active material for a secondary battery, comprising silicate composite particles including a silicate phase and a silicon phase, wherein the silicon phase is dispersed in the silicate phase, and the silicon phase contains phosphorus in addition to silicon.

[0012] Another aspect of the present invention relates to a secondary battery comprising a negative electrode, a positive electrode, and a non-aqueous electrolyte, wherein the negative electrode contains the negative electrode active material for a secondary battery.

[0013] Effects of the Invention

[0014] By incorporating phosphorus into the silicon phase, the electronic conductivity of the silicon phase is improved, and the powder resistivity of the silicate composite particles is reduced, resulting in an improvement in the initial charge and discharge efficiency.

[0015] The novel features of the present invention are set forth in the appended claims, both as to structure and content, together with other objects and features of the present invention, and will be better understood from the following detailed description with reference to the accompanying drawings. BRIEF DESCRIPTION OF THE DRAWINGS

[0016] Figure 1 This is a cross-sectional view schematically showing silicate composite particles according to one embodiment of the present invention.

[0017] Figure 2 This is a schematic perspective view showing a secondary battery according to an embodiment of the present invention with a portion cut away. DETAILED DESCRIPTION

[0018] Hereinafter, embodiments of the present disclosure will be described with examples, but the present disclosure is not limited to the examples described below. In the following description, specific numerical values ​​or materials are sometimes exemplified, but other numerical values ​​or materials may also be applied as long as the effects of the present disclosure can be obtained. In this specification, the description of "numerical value A to numerical value B" includes numerical value A and numerical value B, which may be replaced by "above numerical value A and below numerical value B". In the following description, when the lower limit and upper limit of numerical values ​​related to specific physical properties or conditions are exemplified, as long as the lower limit is not above the upper limit, any one of the exemplified lower limits and any one of the exemplified upper limits may be arbitrarily combined. When multiple materials are exemplified, one may be selected and used alone, or two or more may be used in combination.

[0019] In addition, the present disclosure includes a combination of matters recorded in two or more claims arbitrarily selected from the plurality of claims recorded in the attached claims. In other words, matters recorded in two or more claims arbitrarily selected from the plurality of claims recorded in the attached claims may be combined as long as no technical contradiction arises.

[0020] In the following description, the term “comprising” or “including” includes “comprising (or including)”, “consisting essentially of” and “consisting of”.

[0021] Secondary batteries include at least non-aqueous electrolyte secondary batteries such as lithium ion batteries, lithium metal secondary batteries, and all-solid batteries.

[0022] The negative electrode active material for a secondary battery according to the present embodiment comprises silicate composite particles. Silicate composite particles refer to particles containing a silicate phase and other materials. Here, silicate composite particles are particles containing a silicate phase and a silicon phase. The silicon phase is dispersed in the silicate phase. The silicon phase contains phosphorus (P).

[0023] The silicon phase containing phosphorus (P) may be, for example, a phase composed of 90 atomic % or more of silicon. At least a portion of the silicon phase may be a phase of a single substance of silicon (Si). The silicon phase may be amorphous or may be composed of tiny crystal grains (microcrystals).

[0024] The silicon phase may be a particle-like phase. The silicon phase may also be a phase other than a particle-like phase. The silicate composite particle may have a sea-island structure, in which the silicate phase constitutes a sea portion (matrix) and the silicon phase constitutes a plurality of island portions. Adjacent particle-like phases may be partially continuous. The silicon phase may be a network-like phase.

[0025] The silicate composite particles are produced, for example, by mixing silicate powder and silicon particles, pulverizing the mixture using a ball mill or the like, and sintering the pulverized mixture in a high-temperature and high-pressure atmosphere.

[0026] The silicate composite particles having the above structure can arbitrarily control the capacity by controlling the amount of the silicon phase dispersed in the silicate phase. Thus, the high capacity of the silicate composite particles can be achieved. In addition, since the silicon phase is dispersed in the silicate phase, the stress associated with the expansion and contraction of the silicon phase during charging and discharging is alleviated by the silicate phase. Therefore, the cracking and breaking of the silicate composite particles can be reduced. In addition, it is easy to take into account both the high capacity of the battery and the improvement of the cycle characteristics.

[0027] By introducing phosphorus into the silicon phase, it is considered that the initial charge and discharge efficiency is improved for the following reason.

[0028] First, the silicon phase is heated during the manufacturing process of the silicate composite particles. In the case where a coating layer (e.g., a conductive coating layer containing a carbon material) is formed on the surface of the silicate composite particles, the silicate composite particles are heated to a high temperature together with the raw materials of the coating layer in the process. Heating has the effect of promoting the crystal growth of silicon. On the other hand, in the case where phosphorus is introduced into the silicon phase, the crystal growth of silicon during heating is hindered by the presence of phosphorus. As a result, the crystallite size of the silicon phase can be reduced. The smaller the crystallite size, the easier it is to relax the stress caused by the expansion and contraction of the silicon phase. As a result, during the initial charge and discharge, when the silicon phase expands and then contracts, the electronic conduction network of the silicon phase is not easily cut off. As a result, it is easy to take into account both the improvement of the initial charge and discharge efficiency and the improvement of the cycle characteristics. In addition, the effect of reducing the cracking and rupture of the silicate composite particles can also be improved.

[0029] Secondly, the phosphorus element contained in the silicon phase has the effect of improving the electronic conductivity of the silicon phase itself. As a result, the powder resistivity of the silicate composite particles becomes smaller, and the initial charge and discharge efficiency is improved. Since the electronic conductivity of the silicate phase is low, most of the electronic conduction network in the silicate composite particles is formed by the silicon phase. When the electronic conductivity of the silicon phase itself is improved, even if the electronic conduction network of the silicon phase is partially cut off during the initial charge and discharge, it is not easily affected by such cut-off. Therefore, the initial charge and discharge efficiency is further improved.

[0030] The mechanism for improving the electronic conductivity of the silicon phase is speculated as follows. It is believed that at least a portion of the phosphorus element is replaced in the form of phosphorus atoms in the lattice site of silicon in the silicon phase. By doping the lattice of silicon (Si) with a valence of four with phosphorus (P), excess electrons for maintaining electrical neutrality are introduced into the silicon phase. As a result, it is believed that the electronic conductivity of the silicon phase is significantly improved. Phosphorus atoms can be dissolved in the silicon phase to form a solid solution.

[0031] In addition, the silicon phase gradually deforms through repeated charge and discharge. For example, in the silicate composite particles with a sea-island structure, the adjacent islands (silicon phases) partially contact each other, which can make the electron conduction network strong. As a result, the charge and discharge efficiency is further improved and not only in the initial stage. The silicon phase can form a mesh-like electron conduction network during the charge and discharge cycle.

[0032] Phosphorus (P) may exist in the silicon phase in any form such as a simple substance, a compound, a polyanion, a free radical, or an atom.

[0033] In the silicon phase, at least a portion of the phosphorus element may form a PO structure. For example, the phosphorus element may form a polyanion having a stable bond with an oxygen atom. Since oxygen atoms have a high affinity with both silicon atoms and phosphorus atoms, the oxygen-containing polyanion is easily doped into the silicon phase.

[0034] In the PO structure, the bond between P and O can be a single bond (PO), a double bond (P=O), or a bond in between.

[0035] The PO structure can be contained in a phosphoric acid compound such as a phosphate anion, a phosphite anion, a phosphonate anion, a phosphinate anion, etc. Among them, it is preferred that the PO structure constitutes a PO3 structure because it is easy to contain the silicon phase and the raw material phosphoric acid is cheap.

[0036] The PO3 structure can be included in the PO3 3- 、HPO3 2- 、H2PO3 - Such polyanions can form salts such as phosphates.

[0037] In the spectrum obtained by X-ray photoelectron spectroscopy (XPS) of the silicon phase containing the PO 3 structure, a peak derived from the PO 3 structure is observed in the range of 134.0 to 134.6 eV.

[0038] The size of the crystallites constituting the silicon phase (hereinafter also referred to as "crystallite size") is, for example, less than 30 nm, less than 20 nm, or less than 15 nm. In this case, the volume change caused by the expansion and contraction of the silicon phase accompanying the charge and discharge can be reduced, and the charge and discharge efficiency and cycle characteristics can be improved. There is no particular limitation on the lower limit of the crystallite size of the silicon phase, for example, 1 nm. An example of a preferred range of the crystallite size of the silicon phase is greater than 1 nm and less than 20 nm.

[0039] The crystallite size of the silicon phase was calculated by the Scherrer equation from the half-value width of the diffraction peak attributed to the Si (111) plane in the X-ray diffraction (XRD) pattern of the silicon phase.

[0040] The average particle size of the silicon phase (the average particle size of the island portion in the case of the sea-island structure) can be, for example, 1 nm or more, or 5 nm or more. The average particle size is, for example, 1000 nm or less, 500 nm or less, 200 nm or less, 100 nm or less, or 50 nm or less. Such a fine silicon phase has a small volume change during charge and discharge, and is preferred in terms of improving the structural stability of the silicate composite particles. An example of a preferred range of the average particle size of the silicon phase is 1 nm or more and 1000 nm or less.

[0041] The average particle size of the silicon phase can be measured by observing the cross section of the silicate composite particles using a SEM (scanning electron microscope) or a TEM (transmission electron microscope). Specifically, the maximum diameters of any 100 granular or island-shaped silicon phases are averaged and determined.

[0042] The content of phosphorus contained in the silicon phase only needs to be within a range that does not greatly damage the capacity of the silicon phase. If it is within such a range, the silicon phase may contain phosphorus in an amount exceeding the solid solution limit of phosphorus in the silicon phase. The content of phosphorus contained in the silicon phase may be, for example, less than 10% by mass, or less than 5% by mass. On the other hand, the content of phosphorus contained in the silicon phase may be a trace amount. For example, the content of phosphorus contained in the silicon phase may be more than 0.001% by mass, more than 0.005% by mass, more than 0.01% by mass, or more than 0.2% by mass. An example of a preferred range of the content of phosphorus contained in the silicon phase is more than 0.01% by mass and less than 10% by mass.

[0043] The content of phosphorus contained in the silicon phase can be determined by performing inductively coupled plasma atomic emission spectrometry (ICP-AES) on silicate composite particles taken out of the battery, or by performing energy dispersive X-ray spectrometry (EDX) on an electron image of a cross section of silicate composite particles obtained using a transmission electron microscope (TEM) or a scanning electron microscope (SEM), or by combining these two analyses. Even when both the silicate phase and the silicon phase contain phosphorus, the content of phosphorus contained in the silicon phase can be calculated by using SEM-EDX, for example.

[0044] When EDX is performed, for the cross section of the silicate composite particles, for example, a fully discharged battery is decomposed, the negative electrode is taken out, the negative electrode is cleaned with anhydrous ethyl methyl carbonate or dimethyl carbonate, and after drying, a cross section polisher (CP) is used to obtain the cross section of the negative electrode mixture layer. Then, the cross section of the negative electrode mixture layer is observed using TEM or SEM.

[0045] In the case of IPC-AES, after washing with anhydrous ethyl methyl carbonate or dimethyl carbonate, the negative electrode mixture is peeled off from the dried negative electrode and crushed with a mortar to obtain a sample powder. Next, the sample powder is dried in a dry atmosphere for 1 hour and immersed in weakly boiling 6M hydrochloric acid for 10 minutes. Next, the sample powder is washed with ion exchange water, filtered, and dried at 200°C for 1 hour. Then, it is heated to 900°C in an oxygen atmosphere to remove the carbon component, thereby separating the silicate composite particles.

[0046] The silicate phase contains metal elements M, Si, and O (oxygen). The metal element M preferably contains at least one element E1 selected from alkali metal elements and Group 2 elements. The element E1 may be, for example, at least one selected from Li, Na, K, Cs, Mg, Ca, Sr, and Ba.

[0047] The silicate phase may further contain an element E2 in addition to the element E1. The element E2 may be at least one selected from zirconium, niobium, tantalum, lanthanum, vanadium, titanium, phosphorus, bismuth, zinc, tin, lead, antimony, cobalt, fluorine, tungsten, aluminum and boron.

[0048] Among them, from the perspective of excellent lithium ion conductivity, the silicate phase is preferably a lithium silicate (lithium silicate) phase containing Li as the element E1. That is, the silicate phase preferably has a lithium silicate phase as the main component. In other words, the ratio of Li contained in the silicate phase to the metal element other than Si is preferably 50 atomic % or more, more preferably 70 atomic % or more, and further preferably 90 atomic % or more.

[0049] In the silicate phase, the composition of Si, Li and O is, for example, given by the formula: Li 2z SiO 2+z (0<z<2). The preferred range of z is 0<z<1, and z=1 / 2 is more preferred. In a preferred embodiment, most of Si constitutes lithium silicate. Lithium silicate preferably contains Li2Si2O5 as a main component, and preferably Li2Si2O5 is the main component of the entire silicate phase. Here, the "main component" refers to a component that accounts for more than 50% by mass of the mass of the entire lithium silicate or the entire silicate phase, and may also account for more than 70% by mass.

[0050] The content of each element contained in the silicate phase can be obtained by any of the following methods. In addition, the composition of the silicate phase can be calculated from the content of each element.

[0051] <EDX>

[0052] From the reflected electron image of the cross section of the silicate composite particles described above, 10 composite particles with a maximum diameter of 5 μm or more are randomly selected, and the elements are mapped and analyzed by EDX. The area ratio of the target element is calculated using image analysis software. The observation magnification is preferably 2000 to 20000 times. The measured values ​​of the area ratio of the predetermined element contained in the 10 particles are averaged. The content of the target element is calculated from the obtained average value.

[0053] Preferred measurement conditions for cross-sectional SEM-EDX analysis are shown below.

[0054] <SEM-EDX measurement conditions>

[0055] Processing equipment: JEOL, SM-09010 (Cross Section Polisher)

[0056] Processing conditions: Acceleration voltage 6kV

[0057] Current value: 140μA

[0058] Vacuum degree: 1×10 -3 ~2×10 -3 Pa

[0059] Measuring device: Electron microscope SU-70 manufactured by HITACHI

[0060] Accelerating voltage during analysis: 10kV

[0061] Field: Free Mode

[0062] Probe current mode: Medium

[0063] Probe current range: High

[0064] Anode Ap.: 3

[0065] OBJ AP.:2

[0066] Analysis area: 1μm square

[0067] Analysis software: EDAX Genesis

[0068] CPS: 20500

[0069] Lsec: 50

[0070] Time constant: 3.2

[0071] <AES>

[0072] From the reflected electron image of the cross section of the silicate composite particles, 10 composite particles with a maximum diameter of 5 μm or more are randomly selected, and the elements are qualitatively and quantitatively analyzed using an Auger electron spectrometer (AES) analyzer (e.g., JAMP-9510F manufactured by JEOL Ltd.). The measurement conditions may be, for example, an acceleration voltage of 10 kV, a beam current of 10 nA, and an analysis area of ​​20 μmφ. The contents of the predetermined elements contained in the 10 particles are averaged to calculate the contents.

[0073] In addition, during the charge and discharge process, a film is formed on the surface of the silicate composite particles by decomposition of the non-aqueous electrolyte. The mapping analysis performed by EDX or AES is performed on the range of 1 μm or more from the peripheral edge of the cross section of the composite particles inward in a manner that does not contain a thin film or coating layer in the measurement range. Since it is difficult to distinguish the decomposition products of the non-aqueous electrolyte at the end of the cycle, it is preferred to measure the sample before or at the beginning of the cycle.

[0074] <ICP>

[0075] The silicate composite particle sample was completely dissolved in a heated acid solution (a mixed acid of hydrofluoric acid, nitric acid, and sulfuric acid), and the carbon in the solution residue was filtered out. The resulting filtrate was then analyzed by inductively coupled plasma emission spectrometry (ICP) to measure the spectral intensity of each element. Next, a standard curve was prepared using a commercially available standard solution of the element to calculate the content of each element contained in the composite particle.

[0076] Furthermore, the quantitative analysis of each element can also be performed using electron microanalyzer (EPMA), laser ablation ICP mass spectrometry (LA-ICP-MS), X-ray photoelectron spectroscopy (XPS), or the like.

[0077] The contents of B, Na, K, and Al contained in the silicate phase can be quantitatively analyzed based on JIS R3105 (1995) (analysis method of borosilicate glass).

[0078] A silicate phase and a silicon phase exist in the composite particles. The Si content obtained by the above method is the sum of the amount of Si constituting the silicon phase and the amount of Si in the silicate phase. On the other hand, the amount of Si constituting the silicon phase can be quantified using Si-NMR. Thus, by using Si-NMR, the amount of Si constituting the silicon phase and the amount of Si in the silicate phase can be distinguished and quantified. In addition, as a standard substance required for quantification, a mixture of a silicate phase and a silicon phase containing a known Si content in a predetermined ratio can be used.

[0079] Preferred Si-NMR measurement conditions are shown below.

[0080] <Si-NMR measurement conditions>

[0081] Measuring device: Varian, solid-state nuclear magnetic resonance spectrometer (INOVA-400)

[0082] Probe: Varian 7mm CPMAS-2

[0083] MAS: 4.2kHz

[0084] MAS speed: 4kHz

[0085] Pulse: DD (45° pulse + signal extraction time 1H decoupling)

[0086] Repeat time: 1200sec~3000sec

[0087] Observation width: 100kHz

[0088] Observation center: around -100ppm

[0089] Signal extraction time: 0.05sec

[0090] Total times: 560

[0091] Sample amount: 207.6 mg

[0092] In order to increase the capacity and improve the cycle characteristics, the content of the silicon phase in the silicate composite particles is, for example, 30% by mass or more and 80% by mass or less. By making the content of the silicon phase 30% by mass or more, the proportion of the silicate phase becomes smaller, and it is easy to improve the initial charge and discharge efficiency. By making the content of the silicon phase 80% by mass or less, it is easy to reduce the degree of expansion and contraction of the silicate composite particles during charge and discharge. The content of the silicon phase in the silicate composite particles is preferably 40% by mass or more, and more preferably 50% by mass or more.

[0093] A coating layer may be present on the surface of the silicate composite particles. The coating layer is provided, for example, to improve the conductivity of the silicate composite particles. Such a coating layer may contain a carbon material. The coating layer only needs to cover at least a portion of the surface of the silicate composite particles. Since the silicate phase lacks electronic conductivity, the conductivity of the silicate composite particles is also prone to decrease. In contrast, by having a coating layer containing a conductive material on the surface of the silicate composite particles, the conductivity can be dramatically improved.

[0094] The thickness of the coating layer is preferably thin enough not to substantially affect the average particle size of the silicate composite particles. In order to ensure conductivity and the diffusivity of ions that contribute to charge and discharge, the thickness of the coating layer is preferably 1 to 200 nm, more preferably 5 to 100 nm. The thickness of the coating layer can be measured by observing the cross section of the silicate composite particles using SEM or TEM.

[0095] The carbon material constituting the coating layer preferably contains at least one selected from carbon compounds and carbonaceous materials. As carbon compounds, for example, compounds containing carbon and hydrogen, compounds containing carbon, hydrogen and oxygen can be mentioned. As carbonaceous materials, amorphous carbon with low crystallinity, graphite with high crystallinity, etc. can be used. As amorphous carbon, carbon black, coal, coke, charcoal, activated carbon, etc. can be mentioned. As graphite, natural graphite, artificial graphite, graphitized intermediate phase carbon particles, etc. can be mentioned. Among them, amorphous carbon is preferred from the aspects of low hardness and large buffering effect on the silicon phase whose volume changes due to charging and discharging. Amorphous carbon can be easily graphitized carbon (soft carbon) or difficult to graphitize carbon (hard carbon). As carbon black, acetylene black, Ketjen black, etc. can be mentioned.

[0096] Next, an example of a method for producing silicate composite particles will be described in detail.

[0097] Process (i)

[0098] Prepare lithium silicate. The raw material used is a raw material mixture containing a Si-containing raw material and a Li raw material in a predetermined ratio. The raw material mixture may contain the above-mentioned alkali metal elements, Group 2 elements, and / or element M. The mixture of the above-mentioned raw materials is dissolved, and the molten liquid (melt) is passed through a metal roller to form a thin film to synthesize lithium silicate. Then, in an atmospheric atmosphere, at a temperature above the glass transition point and below the melting point, the thinned lithium silicate is crystallized by heat treatment. In addition, the thinned lithium silicate can also be used without being crystallized. In addition, instead of dissolving the mixture, it is also possible to sinter it at a temperature below the melting point to produce lithium silicate by a solid phase reaction.

[0099] Silicon oxide can be used as Si raw material. For example, lithium carbonate, lithium oxide, lithium hydroxide, lithium hydride, etc. can be used as Li raw material. These can be used alone or in combination of two or more. As raw materials of alkali metal elements, Group 2 elements, and element M, oxides, hydroxides, carbonate compounds, hydrides, nitrates, sulfates, etc. of each element can be cited.

[0100] Unreacted Si raw material may remain in the lithium silicate, and the remaining Si raw material is dispersed in the lithium silicate as a silicon oxide phase.

[0101] Step (ii)

[0102] Raw silicon is added to the prepared lithium silicate to form a composite. The raw silicon contains a predetermined amount of phosphorus (P). For example, silicate composite particles are prepared through the following steps (a) to (c). There is no particular limitation on the method of making the silicon contain phosphorus (P). For example, phosphorus can be doped into the raw silicon by evaporating POCl3 diluted with a mixed gas of nitrogen and oxygen onto silicon at a high temperature. In the case where phosphorus glass is attached to the surface of the silicon doped with phosphorus, the silicon surface is treated with HF to remove the phosphorus glass.

[0103] Process (a)

[0104] The raw silicon powder and the lithium silicate powder are mixed at a mass ratio of 20:80 to 95:5, for example. The raw silicon can be coarse silicon particles with an average particle size of several to several tens of μm. The coarse particles contain a predetermined amount of phosphorus (P).

[0105] Process (b)

[0106] Next, a mixture of raw silicon and lithium silicate is pulverized while being micronized using a pulverizing device such as a ball mill to form a composite. An organic solvent may be added to the mixture to perform wet pulverization. A predetermined amount of organic solvent may be added to the pulverizing container all at once at the beginning of pulverization, or the organic solvent may be added to the pulverizing container intermittently in multiple times during the pulverization process. The organic solvent serves to prevent the pulverized object from adhering to the inner wall of the pulverizing container.

[0107] As the organic solvent, alcohol, ether, fatty acid, alkane, cycloalkane, silicate, metal alkoxide or the like can be used.

[0108] Alternatively, the raw silicon and lithium silicate may be micronized and mixed. Alternatively, instead of using a pulverizing device, silicon nanoparticles and amorphous lithium silicate nanoparticles may be prepared and mixed. Nanoparticles may be prepared by a known method such as a gas phase method (e.g., a plasma method) or a liquid phase method (e.g., a liquid phase reduction method).

[0109] Process (c)

[0110] The mixture is heated to 450°C to 1000°C while being pressurized in an inert gas atmosphere (e.g., an atmosphere of argon, nitrogen, etc.) to be sintered. Sintering can be performed using a sintering device capable of pressurizing in an inert atmosphere, such as hot pressing or spark plasma sintering. During sintering, lithium silicate softens and flows to fill the gaps between silicon particles. As a result, a dense block-shaped sintered body with a silicate phase as a sea portion and silicon particles as an island portion can be obtained.

[0111] If the obtained sintered body is crushed, silicate composite particles can be obtained. By appropriately selecting the crushing conditions, silicate composite particles with a predetermined average particle size can be obtained. The average particle size of the silicate composite particles is, for example, 1 to 20 μm. The average particle size of the silicate composite particles refers to the particle size (volume average particle size) at which the volume cumulative value is 50% in the volume particle size distribution measured by the laser diffraction scattering method.

[0112] Sintering can be performed by rolling a powder of a mixture preformed into a sheet under heating. Rolling is usually performed by passing the mixture sheet through a gap between two rotating rollers. By passing the mixture sheet through the gap between heated rollers, the mixture can be heated and pressurized at the same time. The mixture sheet can also be heated before and / or after passing through the rollers. By rolling the mixture formed into a sheet while performing a heat treatment, silicate composite particles can be produced with high productivity.

[0113] Process (iii)

[0114] At least a portion of the surface of the obtained silicate composite particles can be coated with a conductive material to form a coating layer. The conductive material is preferably electrochemically stable, and a conductive carbon material is preferably used. As a method for coating at least a portion of the surface of the silicate composite particles with a conductive carbon material, a CVD method using hydrocarbon gases such as acetylene and methane as raw materials can be cited. In addition, a method of mixing coal tar, petroleum asphalt, phenolic resin, etc. with silicate composite particles and heating them to carbonize them can also be exemplified. A mixture of silicate composite particles and raw materials of conductive carbon materials such as coal tar, petroleum asphalt, phenolic resin, etc. is heated at 700°C to 950°C in an inert atmosphere (such as an atmosphere of argon, nitrogen, etc.). In addition, carbon black can also be attached to the surface of the silicate composite particles.

[0115] Step (iv)

[0116] A step of washing the silicate composite particles (including the case where the surface has a coating layer) with an acid may be performed. For example, by washing the silicate composite particles with an acidic aqueous solution, a trace amount of alkali components that may be generated when the raw silicon and lithium silicate are composited can be removed. As the acidic aqueous solution, an aqueous solution of an inorganic acid such as hydrochloric acid, hydrofluoric acid, sulfuric acid, nitric acid, phosphoric acid, carbonic acid, or an aqueous solution of an organic acid such as citric acid, acetic acid, etc. can be used.

[0117] In step (c) of step (ii) and step (iii), since the heat treatment is performed at a relatively high temperature, the crystallite size of silicon in the silicate composite particles increases with heating. In contrast, by including phosphorus (P) in the silicon phase, the increase in the crystallite size of silicon can be suppressed.

[0118] Figure 1 A cross-sectional view schematically shows an example of a silicate composite particle 20. A mother particle 23 includes a lithium silicate phase 21 and silicon particles 22 dispersed in the lithium silicate phase 21. The silicon particles 22 contain phosphorus. The mother particle 23 has a sea-island structure 24 in which fine silicon particles are dispersed in a matrix of the lithium silicate phase 21. The surface of the mother particle 23 is coated with a coating layer 26 to form a silicate composite particle 20.

[0119] The mother particle 23 may contain other components in addition to the lithium silicate phase 21 and the silicon particles 22. For example, from the viewpoint of improving the strength of the mother particle 23, a reinforcing material such as an oxide such as ZrO2 or a carbide, a carbon material, a silicon oxide phase, etc., may be contained in an amount of less than 10% by weight relative to the mother particle 23.

[0120] The secondary battery according to the embodiment of the present disclosure includes a positive electrode, a negative electrode, and a non-aqueous electrolyte. A separator may be interposed between the positive electrode and the negative electrode.

[0121] [negative electrode]

[0122] The negative electrode, for example, comprises a negative electrode current collector and a negative electrode mixture layer formed on the surface of the negative electrode current collector and containing a negative electrode active material. The negative electrode mixture layer is composed of a negative electrode mixture. The negative electrode mixture layer can be formed by applying a negative electrode slurry formed by dispersing the negative electrode mixture in a dispersion medium on the surface of the negative electrode current collector and drying it. The dried coating film can be rolled as needed. The negative electrode mixture layer can be formed on one surface of the negative electrode current collector or on both surfaces.

[0123] The negative electrode mixture contains a negative electrode active material as an essential component, and may contain a binder, a conductive agent, a thickener, etc. as an optional component. The negative electrode active material includes the above-mentioned silicate composite particles. The silicate composite particles contain a silicon phase, and thus contribute to the high capacity of the negative electrode.

[0124] The negative electrode active material may also contain other active material materials that electrochemically absorb and release lithium ions. As other active material materials, carbon-based active materials are preferred. The volume of silicate composite particles expands and contracts with charging and discharging. Therefore, if the proportion of silicate composite particles in the negative electrode active material increases, poor contact between the negative electrode active material and the negative electrode collector is likely to occur. On the other hand, by using silicate composite particles and carbon-based active materials in combination, it is possible to achieve excellent cycle characteristics while imparting a high capacity of the silicon phase to the negative electrode. Relative to the total of silicate composite particles and carbon-based active materials, the proportion of silicate composite particles is preferably, for example, 0.5 to 15% by mass, and more preferably 1 to 10% by mass. As a result, it is easy to take into account both high capacity and improved cycle characteristics.

[0125] As carbon-based active materials, for example, graphite, easily graphitized carbon (soft carbon), and difficultly graphitized carbon (hard carbon) can be exemplified. Among them, graphite having excellent charge and discharge stability and low irreversible capacity is preferred. Graphite refers to a material having a graphite-type crystal structure, including, for example, natural graphite, artificial graphite, and graphitized mesophase carbon particles. One carbon-based active material can be used alone, or two or more can be used in combination.

[0126] As the negative electrode current collector, a non-porous conductive substrate (metal foil, etc.) or a porous conductive substrate (grid, mesh, punching plate, etc.) is used. As the material of the negative electrode current collector, stainless steel, nickel, nickel alloy, copper, copper alloy, etc. can be exemplified. The thickness of the negative electrode current collector is not particularly limited, but from the viewpoint of balancing the strength and lightness of the negative electrode, it is preferably 1 to 50 μm, and more preferably 5 to 20 μm.

[0127] Examples of the binder include fluororesins, polyolefin resins, polyamide resins, polyimide resins, vinyl resins, styrene-butadiene copolymer rubber (SBR), polyacrylic acid and derivatives thereof, etc. These may be used alone or in combination of two or more.

[0128] Examples of the conductive agent include carbon black, conductive fibers, carbon fluoride, and organic conductive materials, etc. These may be used alone or in combination of two or more.

[0129] Examples of the thickener include carboxymethyl cellulose (CMC), polyvinyl alcohol, etc. These may be used alone or in combination of two or more.

[0130] Examples of the dispersion medium include water, alcohol, ether, N-methyl-2-pyrrolidone (NMP), and mixed solvents thereof.

[0131] [positive electrode]

[0132] The positive electrode, for example, comprises a positive electrode collector and a positive electrode mixture layer formed on the surface of the positive electrode collector. The positive electrode mixture layer is composed of a positive electrode mixture. The positive electrode mixture layer can be formed by applying a positive electrode slurry formed by dispersing the positive electrode mixture in a dispersion medium on the surface of the positive electrode collector and drying it. The dried coating can be rolled as needed. The positive electrode mixture layer can be formed on one surface of the positive electrode collector or on both surfaces.

[0133] The positive electrode mixture contains a positive electrode active material as an essential component, and may contain a binder, a conductive agent, etc. as optional components.

[0134] As the positive electrode active material, a lithium composite metal oxide can be used. Examples of the lithium composite metal oxide include Li a CoO2、Li a NiO2、Li a MnO2、Li a Co b Ni 1-b O2、Li a Co b M 1-b O c , Li a Ni 1-b M b O c , Li a Mn2O4、Li a Mn 2- b M bO4, LiMePO4, Li2MePO4F. Wherein, M is at least one selected from Na, Mg, Sc, Y, Mn, Fe, Co, Ni, Cu, Zn, Al, Cr, Pb, Sb and B. Me contains at least a transition element (for example, at least one selected from Mn, Fe, Co, Ni). Here, 0≤a≤1.2, 0≤b≤0.9, 2.0≤c≤2.3. In addition, the value a representing the molar ratio of lithium is the value immediately after the active material is made, and increases or decreases according to charge and discharge.

[0135] As the binder and the conductive agent, for example, any material selected from the materials exemplified for the negative electrode can be used. As the conductive agent, graphite such as natural graphite and artificial graphite can be used.

[0136] As the positive electrode collector, a non-porous conductive substrate (metal foil, etc.) or a porous conductive substrate (mesh, mesh, punching plate, etc.) is used. As the material of the positive electrode collector, for example, stainless steel, aluminum, aluminum alloy, titanium, etc. can be exemplified. The thickness of the positive electrode collector is not particularly limited, but from the perspective of balancing the strength and lightness of the positive electrode, it is preferably 1 to 50 μm, and more preferably 5 to 20 μm.

[0137] [Non-aqueous electrolyte]

[0138] The non-aqueous electrolyte has lithium ion conductivity and may be a liquid electrolyte (electrolyte) or a solid electrolyte.

[0139] The liquid electrolyte (electrolyte) contains a solvent and a lithium salt dissolved in the solvent. The concentration of the lithium salt in the electrolytic solution is, for example, 0.5 to 2 mol / L. The electrolytic solution may contain a known additive.

[0140] A non-aqueous solvent is used as the solvent. As the non-aqueous solvent, for example, cyclic carbonates, chain carbonates, cyclic carboxylates, etc. can be used. As cyclic carbonates, propylene carbonate (PC), ethylene carbonate (EC), etc. can be mentioned. As chain carbonates, diethyl carbonate (DEC), ethyl methyl carbonate (EMC), dimethyl carbonate (DMC), etc. can be mentioned. As cyclic carboxylates, γ-butyrolactone (GBL), γ-valerolactone (GVL), etc. can be mentioned. The non-aqueous solvent can be used alone or in combination of two or more.

[0141] As the lithium salt, for example, lithium salts of chlorine-containing acids (LiClO4, LiAlCl4, LiB 10 Cl 10etc.), lithium salts of fluorinated acids (LiPF6, LiBF4, LiSbF6, LiAsF6, LiCF3SO3, LiCF3CO2, etc.), lithium salts of fluorinated acid imides (LiN(FSO2)2, LiN(CF3SO2)2, LiN(CF3SO2)(C4F9SO2), LiN(C2F5SO2)2, etc.), lithium halides (LiCl, LiBr, LiI, etc.), etc. The lithium salts may be used alone or in combination of two or more.

[0142] As the solid electrolyte, for example, a solid or gel-like polymer electrolyte, an inorganic solid electrolyte, etc. can be used. As the inorganic solid electrolyte, a material known in all-solid lithium-ion secondary batteries, etc. can be used. As such a material, for example, an oxide-based solid electrolyte, a sulfide-based solid electrolyte, and a halogen-based solid electrolyte can be cited. The polymer electrolyte, for example, contains a lithium salt and a matrix polymer. The polymer electrolyte may also contain a non-aqueous solvent. As the matrix polymer, for example, a polymer material that absorbs a non-aqueous solvent and gels is used. As the polymer material, fluororesins, acrylic resins, polyether resins, etc. can be cited.

[0143] [Diaphragm]

[0144] It is preferred to sandwich a separator between the positive electrode and the negative electrode. The separator has high ion permeability and has appropriate mechanical strength and insulation. As the separator, a microporous film, a woven fabric, a non-woven fabric, etc. can be used. As the material of the separator, for example, polyolefins such as polypropylene and polyethylene can be used.

[0145] As an example of the structure of a secondary battery, an electrode group in which a positive electrode and a negative electrode are wound with a separator and an electrolyte is contained in an outer body can be cited. Alternatively, instead of a wound electrode group, an electrode group in other forms such as a laminated electrode group in which a positive electrode and a negative electrode are laminated with a separator can be applied. The secondary battery can be, for example, cylindrical, square, coin-shaped, button-shaped, laminated, or any other form.

[0146] Figure 2It is a schematic perspective view of a square secondary battery involved in one embodiment of the present invention with a portion cut away. The battery comprises a square battery case 4 with a bottom, an electrode group 1 and an electrolyte (not shown) housed in the battery case 4, and a sealing plate 5 for sealing the opening of the battery case 4. The electrode group 1 is formed by winding a long strip-shaped negative electrode, a long strip-shaped positive electrode and a separator therebetween around a flat core and then pulling out the core. The sealing plate 5 has a liquid injection port sealed with a sealing plug 8 and a negative terminal 6 insulated from the sealing plate 5 by a gasket 7. The negative electrode collector and the negative terminal 6 are electrically connected via a negative electrode lead 3. The positive electrode collector and the sealing plate 5 are electrically connected via a positive electrode lead 2. A resin frame is arranged on the upper part of the electrode group 1, which separates the electrode group 1 from the sealing plate 5 and separates the negative electrode lead 3 from the battery case 4.

[0147] Hereinafter, the present disclosure will be described in detail based on examples and comparative examples. However, the present invention is not limited to the following examples.

[0148] <Examples 1 to 3>

[0149] [Preparation of silicate]

[0150] Lithium carbonate and silicon dioxide were mixed in a molar ratio of Li2CO3:SiO2=34:66, and the mixture was heated at 1500°C for 5 hours in an inert gas atmosphere to dissolve it, and the molten liquid was passed through a metal roller to form a sheet, and the sheet product was heated at 750°C for 5 hours to generate lithium silicate. Then, the lithium silicate was crushed to an average particle size of 10 μm.

[0151] [Preparation of Silicate Composite Particles]

[0152] Lithium silicate having an average particle size of 10 μm and coarse particles of silicon (average particle size of 10 μm) containing phosphorus (P) at the content shown in Table 1 were mixed at a mass ratio of 40:60. The mixture was filled into a pot (SUS, volume: 500 mL) of a planetary ball mill (manufactured by Fritsch, P-5), and 24 SUS balls (diameter 20 mm) were placed, and the lid was closed. The mixture was pulverized at 200 rpm in an inert atmosphere for 25 hours to composite silicon with lithium silicate.

[0153] In the spectrum of silicon coarse particles containing phosphorus (P) obtained by X-ray photoelectron spectroscopy, a peak derived from a PO 3 structure was observed in the vicinity of 134.0 to 134.6 eV.

[0154] Then, the crushed product was press-formed into a sheet with a thickness of 4 to 5 mm at room temperature to obtain a sheet-shaped molded body. The molded body was rolled between calendering rolls while heated to 800°C to obtain a sintered body. The rolling was performed in a manner that a pressure of 240 MPa was applied to the molded body. The sintered body was crushed and passed through a 40 μm mesh to obtain silicate composite particles.

[0155] [Formation of coating layer]

[0156] The silicate composite particles were mixed with coal tar pitch (MCP250 manufactured by JFE Chemical Co., Ltd.), and the mixture was calcined at 800°C for 5 hours in an inert atmosphere to form a conductive carbon coating layer on the surface of the silicate composite particles. The mass ratio of the coating layer to the total mass of the silicate composite particles and the coating layer was 5%. Then, a sieve was used to obtain silicate composite particles having an average particle size of 5 μm with the coating layer.

[0157] The composite crushed product before sintering (before press forming into a sheet) (pre-sintering particle A) and the silicate composite particle with a coating layer after sintering (post-sintering particle B) were subjected to XRD analysis to measure the half-value width of the peak from the (111) plane of Si. The crystallite size was calculated using the Scherrer equation based on the half-value width of the peak.

[0158] Table 1 shows the crystallite size of the silicon phase contained in the pre-sintering particles A and the post-sintering particles B, and the volume resistivity (powder resistivity).

[0159] Furthermore, by analyzing the cross section of the silicate composite particles by SEM-EDX using the above method, it was confirmed that phosphorus was contained in the silicon phase at the content ratio shown in Table 1. On the other hand, phosphorus was not detected in the silicate phase.

[0160] Composite silicate particles obtained by using coarse silicon particles having phosphorus (P) contents of 0.01 mass %, 0.1 mass %, and 1 mass % are referred to as composite silicate particles A1, A2, and A3, respectively.

[0161] Table 1

[0162]

[0163] [Production of negative electrode]

[0164] Silicate composite particles and graphite were mixed in a mass ratio of (5-20): (95-80) and used as negative electrode active material. Negative electrode active material, sodium carboxymethyl cellulose (CMC-Na), styrene-butadiene rubber (SBR), and lithium polyacrylate were mixed in a mass ratio of 96.5:1:1.5:1, and after adding water, a mixer was used to stir to prepare negative electrode slurry. Next, a layer of 100% slurry was added to the surface of the copper foil at a rate of 100% slurry per 1 m2 The negative electrode slurry was applied in a manner that the mass of the negative electrode mixture was 190 g, and after the coating was dried, it was rolled to form a copper foil with a density of 1.5 g / cm 3 The negative electrode of the negative electrode mixture layer.

[0165] The negative electrode was cut into a 20 mm × 20 mm shape with a 5 mm × 5 mm protrusion, and the negative electrode mixture layer of the protrusion was peeled off to expose the copper foil. Then, a negative electrode tab lead was connected to the exposed portion of the negative electrode current collector, and a predetermined area around the negative electrode tab lead was covered with an insulating film.

[0166] [Fabrication of Counter Electrode]

[0167] A tab was prepared by welding a small piece of Ni mesh to the end, and the mesh was cut into a predetermined size. The mesh was pressed onto a lithium metal foil having a thickness of 300 μm to prepare a counter electrode.

[0168] [Preparation of non-aqueous electrolyte]

[0169] A non-aqueous electrolyte was prepared by dissolving LiPF6 in a mixed solvent of ethylene carbonate (EC), ethyl methyl carbonate (EMC) and dimethyl carbonate (DMC) at a volume ratio of EC:EMC:DMC=4:1:15. The LiPF6 concentration was 1.3 mol / L.

[0170] [Cell production]

[0171] Use the above-mentioned negative electrode and two counter electrodes to make a unit with negative electrode specifications. Clamp the negative electrode with a pair of counter electrodes, and make the negative electrode mixture layer and the lithium metal foil face each other through the separator to obtain an electrode group. Next, fold the Al laminated film cut into a rectangular shape in half, and heat-seal the two ends of the long side to make a tube shape. Then, put the prepared electrode group into the tube from one side of the short side, align the end face of the Al laminated film with the position of the insulating film of each connector lead, and heat-seal it. Next, inject 0.3cm from the short side of the tube that is not heat-sealed. 3 After the injection, the negative electrode mixture layer was allowed to stand for 3 minutes under a reduced pressure of 0.02 MPa, and then returned to atmospheric pressure. This operation was repeated twice to impregnate the negative electrode mixture layer with the non-aqueous electrolyte. Finally, the end face of the Al laminated film on the injection side was heat-sealed while reducing the pressure to obtain the evaluation unit C1. The production of the unit C1 was carried out in a dry air atmosphere with a dew point below -60°C.

[0172] [evaluate]

[0173] At an ambient temperature of 25°C, the cell was clamped with a pair of 10×5cm stainless steel clamps and fixed with a pressure of 1MPa. Then, the negative electrode was charged with lithium at a constant current of 0.1C until the cell voltage reached 1.000V, then the negative electrode was charged with lithium at a constant current of 0.01C until the cell voltage reached 1.000V, and finally the negative electrode was charged with lithium at a constant current of 0.001C until the cell voltage reached 1.000V. After stopping for 3 hours, a constant current discharge of 0.1C was performed until the cell voltage reached 0.005V. Then, the ratio of the discharge capacity to the charge capacity was calculated as the initial charge and discharge efficiency. The results are shown in Table 2.

[0174] Table 2

[0175]

[0176] <Comparative Example 1>

[0177] Silicate composite particles B1 were prepared in the same manner as in Example 1 except that coarse silicon particles (average particle size 10 μm) containing no phosphorus (P) were used in the preparation of silicate composite particles, and secondary batteries were prepared and evaluated in the same manner.

[0178] <Comparative Example 2>

[0179] Silicate composite particles B2 were prepared in the same manner as in Example 1 except that coarse silicon particles (average particle size 10 μm) containing germanium (Ge) at a content of 1% by mass were used, and secondary batteries were prepared and evaluated in the same manner. The results are shown in Tables 1 and 2.

[0180] From the results in Table 1, it can be understood that by including phosphorus in the silicon phase, the growth of the crystallite size of silicon is suppressed and the volume resistivity of the silicate composite particles is significantly reduced. Reflecting this result, in Table 2, the initial charge and discharge efficiency of the unit using silicate composite particles A1 to A3 is significantly improved. On the other hand, even when phosphorus is included in the silicon phase, the absolute value of the discharge capacity does not change much.

[0181] (Note)

[0182] According to the above records, the following technical solutions are disclosed.

[0183] (Technical Solution 1)

[0184] A negative electrode active material for a secondary battery comprises silicate composite particles containing a silicate phase and a silicon phase, wherein the silicon phase is dispersed in the silicate phase, and the silicon phase contains phosphorus in addition to silicon.

[0185] (Technical Solution 2)

[0186] According to the negative electrode active material for a secondary battery according to claim 1, in the silicon phase, at least a part of the phosphorus element is substituted in a lattice site of silicon in the form of phosphorus atoms.

[0187] (Technical Solution 3)

[0188] According to the negative electrode active material for a secondary battery according to claim 1 or 2, in the silicon phase, at least a part of the phosphorus element forms a PO structure.

[0189] (Technical Solution 4)

[0190] According to any one of technical solutions 1 to 3, the PO structure is included in the PO3 structure, and a peak derived from the PO3 structure is observed in the range of 134.0 eV to 134.6 eV in the spectrum obtained by X-ray photoelectron spectroscopy.

[0191] (Technical Solution 5)

[0192] According to any one of claims 1 to 4, in the negative electrode active material for a secondary battery, an average particle diameter of the silicon phase is 1 nm or more and 1000 nm or less.

[0193] (Technical Solution 6)

[0194] According to any one of claims 1 to 5 , the negative electrode active material for a secondary battery, wherein the silicon phase contains phosphorus element at a content of 0.01 mass % or more and 10 mass % or less.

[0195] (Technical Solution 7)

[0196] According to any one of claims 1 to 6, the negative electrode active material for a secondary battery, the silicate phase contains at least one element E1 selected from alkali metal elements and Group 2 elements.

[0197] (Technical Solution 8)

[0198] According to any one of technical solutions 1 to 7, the negative electrode active material for a secondary battery, the silicate phase further contains element E2, and the element E2 is at least one selected from zirconium, niobium, tantalum, lanthanum, vanadium, titanium, phosphorus, bismuth, zinc, tin, lead, antimony, cobalt, fluorine, tungsten, aluminum and boron.

[0199] (Technical Solution 9)

[0200] According to any one of technical solutions 1 to 8, the negative electrode active material for a secondary battery, in the silicate phase, the composition of Li, Si and O is represented by the formula: Li 2z SiO 2+z It means that in the above formula, 0<z<2 is satisfied.

[0201] (Technical Solution 10)

[0202] According to any one of claims 1 to 9, the negative electrode active material for a secondary battery comprises a coating layer on the surface of the silicate composite particles, and the coating layer contains a carbon material.

[0203] (Technical Solution 11)

[0204] A secondary battery comprises a negative electrode, a positive electrode and a non-aqueous electrolyte, wherein the negative electrode contains the negative electrode active material for a secondary battery as described in any one of claims 1 to 10.

[0205] Industrial Availability

[0206] According to the present disclosure, a secondary battery having high capacity and good charge and discharge efficiency (especially initial charge and discharge efficiency) can be provided. The secondary battery of the present disclosure can be used as a main power source for mobile communication devices, portable electronic devices, and the like.

[0207] The present invention has been described in conjunction with the currently preferred embodiments, but this disclosure should not be interpreted as limiting. By reading the above disclosure, a person of ordinary skill in the art to which the present invention belongs can clearly understand various modifications and changes. Therefore, the appended claims should be interpreted as including all modifications and changes without departing from the true spirit and scope of the present invention.

[0208] Description of Reference Numerals

[0209] 1: electrode group, 2: positive electrode lead, 3: negative electrode lead, 4: battery case, 5: sealing plate, 6: negative electrode terminal, 7: gasket, 8: plug, 20: silicate composite particles, 21: lithium silicate phase, 22: silicon particles, 23: mother particles, 24: sea island structure, 26: coating layer

Claims

1. A negative electrode active material for a secondary battery, comprising silicate composite particles containing a silicate phase and a silicon phase, The silicon phase is dispersed in the silicate phase, The silicon phase contains phosphorus element in addition to silicon.

2. The negative electrode active material for a secondary battery according to claim 1, In the silicon phase, at least a portion of the phosphorus element is substituted into a lattice site of silicon in the form of phosphorus atoms.

3. The negative electrode active material for a secondary battery according to claim 1, In the silicon phase, at least a portion of the phosphorus element forms a PO structure.

4. The negative electrode active material for a secondary battery according to claim 3, The PO structure is contained in the PO3 structure, In the range of 134.0 eV to 134.6 eV in the spectrum obtained by X-ray photoelectron spectroscopy, a peak derived from the PO 3 structure was observed.

5. The negative electrode active material for a secondary battery according to claim 1, The average grain size of the silicon phase is greater than or equal to 1 nm and less than or equal to 1000 nm.

6. The negative electrode active material for a secondary battery according to claim 1, The silicon phase contains phosphorus element at a content of 0.01 mass % or more and 10 mass % or less.

7. The negative electrode active material for a secondary battery according to claim 1, The silicate phase contains at least one element E1 selected from alkali metal elements and Group 2 elements.

8. The negative electrode active material for a secondary battery according to claim 1, The silicate phase also contains element E2, The element E2 is at least one selected from zirconium, niobium, tantalum, lanthanum, vanadium, titanium, phosphorus, bismuth, zinc, tin, lead, antimony, cobalt, fluorine, tungsten, aluminum and boron.

9. The negative electrode active material for a secondary battery according to claim 1, In the silicate phase, the composition of Li, Si and O is given by the formula: Li 2z SiO 2+z express, In the above formula, 0<z<2 is satisfied.

10. The negative electrode active material for a secondary battery according to claim 1, There is a coating layer on the surface of the silicate composite particles, The coating layer contains a carbon material.

11. A secondary battery comprising a negative electrode, a positive electrode and a non-aqueous electrolyte, The negative electrode contains the negative electrode active material for a secondary battery according to any one of claims 1 to 10.

Citation Information

Patent Citations

  • Negative electrode active material for non-aqueous electrolyte secondary cell, and non-aqueous electrolyte secondary cell

    WO2019065766A1

  • Negative electrode active material for secondary batteries, and secondary battery

    WO2021153078A1